DEBAT TENTANG IMAM PEDOFIL DAN TANTANGAN PENDIDIKAN IMAM - Paulinus Yan Olla (Jurnal Orientasi Baru, 2011)
The debate regarding pedophile priests has cornered the Catholic Church.Vigorous press campaigns have shaped public opinion about the Church as asafe haven for the perpetrators. Studies on the problem show that only a smallnumber of priests are pedophiles, in a comparison with other religious groupsor associations. Groups who give vigorous criticism of the Church in fact aresupporters of pedophilia both culturally and politically. This paper would liketo emphasize that the Church recognizes the existence of pedophilia among hermembers. But the Church has also decided to run a zero tolerance policy towardpedophile priests through law enforcement and educational reforms.